Myocardial contractility dysfunction in patients with chronic lymphocytic leukemia receiving chemotherapy and their treatment with enalapril - Davydkin, I. L.; Kuzmina, T. P.; Zolotovskaya, I. A.; Tereshina, O. V.; Danilova, O. E.; Khairetdinov, R. K.; Rogozina, L. A. (Rossiĭskiĭ kardiologicheskiĭ zhurnal, 2020)
Aim. To assess eft ventricular (LV) contractility dysfunction in patients with chronic lymphocytic leukemia (CLL) receiving chemotherapy with fludarabine, cyclophosphamide, and rituximab (FCR), and to determine the enalapril.effectiveness for their treatment. Material and methods. The study included 49 patients with newly diagnosed Binet stage B CLL in combination with class I-II stable angina, stage 1-2 hypertension and LV ejection fraction (EF) >50%. All subjects did not take angiotensin converting enzyme inhibitors (ACE inhibitors), had no clinical signs of heart failure (HF), and all had indications for FCR combination use before study start. Patients underwent two-dimensional echocardiography initially, before starting chemotherapy (period V1) and after three (84±5 days) (V2) and six (168±7 days) (V3) courses of chemo therapy (enalapril) was added to the treatment regimen in the experimental group. Results. After the third course of chemotherapy, a relative percentage decrease in global longitudinal strain (GLS) was noted in the experimental and control groups — by 16,16±0,80 and 16,2±0,79, respectively (p=0,764). These changes are considered a cardiotoxicity predictor. At the same time, LVEF values remained within the normal range: 63,4% [65; 68] in the experimental group and 63,9% [61,6; 67] in the control group (p=0,960). After the sixth course, LVEF values significantly differed (p=0,002): in the control group, five patients (21%) had cardiotoxicity; in experimental group, there were no patients with cardiotoxicity. Conclusion. A clinically significant decrease in GLS is a marker of subclinical LV contractile dysfunction and is a cardiotoxicity predictor in CLL patients receiving chemotherapy with FCR. The timely addition of enalapril to the treatment regimen can prevent cardiotoxicity in such patients. The need for early assessment of GLS during FCR courses for the detection and prevention of cardiotoxicity has been proved.